PERAN DIPLOMASI INDONESIA DALAM PENYELESAIAN KONFLIK ISRAEL-HIZBULLAH DI LEBANON - Nabila, Kania Salsa (LPPM Universitas Bina Bangsa, 2025)
The armed conflict in Lebanon between the armed group Hezbollah and Israel occurred in 2006. Israel's attacks on Middle Eastern countries led to the destruction of civilian infrastructure and largescale displacement, as well as casualties among civilians and military. The United Nations (UN) is responsible for peacekeeping through cooperation with UN member states, including Indonesia. Indonesia demonstrated its role as an active participant in peacekeeping efforts by deploying peacekeeping troops, part of the United Nations Interim Force in Lebanon (UNIFIL), to Lebanon. This study aims to identify and analyze Indonesia's contribution to the resolution of international disputes related to the Israel-Hezbollah conflict in Lebanon. The study will serve as a basic guide to emphasize Indonesia's commitment to world peace, as mandated in the UUD 1945.